The Equator Project Research School and Mentoring Network: Evaluated Interventions to Improve Equity in Geoscience Research - Natasha Dowey; Anya Lawrence; Munira Raji; Christopher Jackson; Rebecca Williams; Ben Fernando; Sam Giles; Jenni Barclay; Louisa Brotherson; Ethny Childs; Jacqueline Houghton; Anjana Khatwa; et al. (Earth Science, Systems and Society)
There is a well-documented racial and ethnic diversity crisis in Geography, Earth and Environmental Sciences (GEES) subjects in the Global North that leads to inequities in who does environmental research. The Equator project set out to increase participation and retention of UK-domiciled Black, Asian and minority ethnic students in GEES research by developing evidence-based, ring-fenced, fully remunerated interventions. These interventions were co-created with and informed by the voices of students and professionals within the GEES community, following a Theory of Change-based, action research approach. The Equator Research School brought together 30 Black, Asian and minority ethnic students in GEES, and 12 academics, professionals and mentors, from across the UK for a 5-day residential workshop in April 2022. The Research School was designed to facilitate network-building, improve awareness of research careers, enhance confidence in continuing in research, and strengthen a sense of belonging in GEES research for participants. The Equator Mentoring Network, which took place from January to May 2022, facilitated networking between 10 Black, Asian and minority ethnic student mentees and 20 academic and industry mentors involved in GEES subject areas. The overall goal of the Mentoring Network was to increase retention of Black, Asian and minority ethnic students into postgraduate research and to improve their overall experience. Evaluation of these interventions took the form of surveys to capture thoughts and reflections before, during and after interventions. Participants in both interventions provided very positive feedback; the majority of those involved felt a stronger sense of belonging and inclusion in GEES research and were more likely to consider a research career after taking part. The evaluation process showed unequivocally that the ring-fenced, discipline-specific, fully funded nature of the interventions was a critical factor in participant involvement. The work led to the development of recommendations for creating successful interventions for improving participation and retention in research, as well as templates for future, related EDI activities.